2007
DOI: 10.1192/pb.bp.106.010389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a crisis resolution and home treatment team on in-patient admissions

Abstract: Aims and MethodTo evaluate the effects of a crisis resolution and home-based treatment team upon in-patient admission rates. We collected data for 2 years prior and 1 year post-implementation of such a service in Leeds. The chosen time frame allowed the new service to settle in and controlled for seasonal variations.ResultsThere were 4353 admissions during the period of the study, with 3325 in the 2 years prior to the service and 1028 in the year after. Generalised linear analysis found a 37.5% reduction in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 4 publications
(3 reference statements)
2
25
0
2
Order By: Relevance
“…Our findings provide evidence to support most previous studies, [5][6][7][8][9][10]12,13 which demonstrated that CRHT teams reduce admission rates and reduce length of in-patient stay. Tyrer et al 11 found a non-significant reduction of 7.7% in admissions following the introduction of a CRHT in Cardiff, but they examined a control population in which they found the same reduction of 7.7% in admissions, which they acknowledge consisted of a population so dissimilar in size and socioeconomic circumstances that it was effectively incomparable with the test group.…”
Section: Contextsupporting
confidence: 82%
See 2 more Smart Citations
“…Our findings provide evidence to support most previous studies, [5][6][7][8][9][10]12,13 which demonstrated that CRHT teams reduce admission rates and reduce length of in-patient stay. Tyrer et al 11 found a non-significant reduction of 7.7% in admissions following the introduction of a CRHT in Cardiff, but they examined a control population in which they found the same reduction of 7.7% in admissions, which they acknowledge consisted of a population so dissimilar in size and socioeconomic circumstances that it was effectively incomparable with the test group.…”
Section: Contextsupporting
confidence: 82%
“…Reduced admission rates have been demonstrated by other studies, including a large observational study of 229 of 303 teams in England. 6,7 A number of investigations have also showed reduced length of in-patient stay following introduction of CRHT. [8][9][10] Crisis resolution and home treatment teams have now been implemented throughout England and Wales.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported that CRTs contribute to reducing rates of acute psychiatric admissions [11][12][13][14] and shortening length of in-patient stay 11,14 . Tyrer et al 15 found a reduction in voluntary admissions following contact with CRTs, but this was offset by a greater number of involuntary admissions.…”
mentioning
confidence: 99%
“…Some positive findings can be reported. When the model is implemented with relatively high fidelity, including 24hour cover and gatekeeping, congruent evidence from national beduse data (Glover 2006), naturalistic investigations of the effects of implementing the model within catchment areas (Johnson 2005a;Jethwa 2007;Keown 2007;Barker 2011) and a randomised controlled trial (Johnson 2005b) shows that reductions in numbers of admissions occur, with accompanying falls in costs (McCrone 2009a,b). Greater satisfaction among service users has also been reported in some CRT studies (Johnson 2005a,b;Winness 2010;Barker 2011), although we know little about the views of carers regarding the current UK model.…”
Section: Evidence: the Positivementioning
confidence: 99%